Museum Genomics Reveals Temporal Genetic Stasis and Global Genetic Diversity in Arabidopsis thaliana - Lua Lopez; Patricia L. M. Lang; Stephanie Marciniak; Logan Kistler; Sergio M. Latorre; Asnake Haile; Eleanna Vasquez Cerda; Diana Gamba; Yuxing Xu; Patrick Woods; Mistire Yifru; Jeffrey Kerby; et al. (Molecular Ecology, 2025)
Global patterns of population genetic variation through time offer a window into evolutionary processes that maintain diversity. Over time, lineages may expand or contract their distribution, causing turnover in population genetic composition. At individual loci, migration, drift and selection (among other processes) may affect allele frequencies. Museum specimens of widely distributed species offer a unique window into the genetics of understudied populations and changes over time. Here, we sequenced genomes of 130 herbarium specimens and 91 new field collections of Arabidopsis thaliana and combined these with published genomes. We sought a broader view of genomic diversity across the species and to test if population genomic composition is changing through time. We documented extensive and previously uncharacterised diversity in a range of populations in Africa, populations that are under threat from anthropogenic climate change. Through time, we did not find dramatic changes in genomic composition of populations. Instead, we found a pattern of genetic change every 100 years of the same magnitude seen when comparing Eurasian populations that are 185 km apart, potentially due to a combination of drift and changing selection. We found only mixed signals of polygenic adaptation at phenology and physiology QTL. We did find that genes conserved across eudicots show altered levels of directional allele frequency change, potentially due to variable purifying and background selection. Our study highlights how museum specimens can reveal new dimensions of population diversity and show how wild populations are evolving in recent history.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Status and future of the forest health indicators program of the USA - Christopher William Woodall; Michael C. Amacher; William A. Bechtold; John W. Coulston; Sarah Jovan; Charles H. Perry; KaDonna C. Randolph; Beth K. Schulz; Gretchen C. Smith; Borys Tkacz; Susan Will-Wolf (Environmental Monitoring and Assessment, 2011)

Virtual observatories for space and solar physics research - Christopher C. Harvey; Michel Gangloff; Todd King; Christopher H. Perry; D. Aaron Roberts; James R. Thieman (Earth Science Informatics, 2008)

Steadiness of quadriceps contractions in young and older adults with and without a history of falling - Serena F. Carville; Mark C. Perry; Olga M. Rutherford; I Christopher H. Smith; Di J. Newham (European Journal of Applied Physiology, 2007)

Strength, power output and symmetry of leg muscles: effect of age and history of falling - Mark C. Perry; Serena F. Carville; I. Christopher H. Smith; Olga M. Rutherford; Di J. Newham (European Journal of Applied Physiology, 2007)